PRODUCT PROMOTION STRATEGY AND FINANCIAL STATEMENS IN THE PANDEMIC ERA FOR GENTENG KREATIF – SMEs GROUP SURABAYA - Rizka Miladiah Ervianty; Yanuar Nugroho; Anisa Fitri Sya'bania (Universitas Airlangga, 2020)
MSMEs were originally an important contributor to gross domestic product of more than 60%, but the crisis caused by Covid-19 has caused a global economic recession which has also reduced the turnover of MSMEs nationally because there are still many that rely on offline marketing, including who are members of the Genteng Kreatif Association. Given that the MSME sector is one of the drivers of the domestic economy and has a large labor absorption rate, saving the MSMEs sector is currently an obligation that must be resolved immediately so that the national economy can recover. This community service activity seeks to contribute as a solution to the problems that are being faced by MSMEs players in the midst of a crisis. This activity has resulted in MSMEs players being able to maximize the use of marketing applications by making effective promotional plans, attracting customer attention, informing potential customers about the product's existence and binding customers with the products offered so that MSME players can be competitive again and contribute again to the economic sector. In addition, the classic problem of business financial recording has also been given a solution to separate business and personal finances.